Causal factors of election violence in Africa : a comparative analysis of Kenya´s 2007 elections and Zimbabwe´s 2008 elections - Timmer, Sanne (Stellenbosch : Stellenbosch University, 2012)
Thesis (MA)--Stellenbosch University, 2012.